Pengaruh Entrepreneurial Learning Terhadap Entrepreneurial Intellectual Capital Dengan Menggunakan Business Incubator Pada Universitas - Virza Utama Alamsyah; Serli Erna Putri; Rexalvador Yana; Delima Rahma; Willyam Andrean (InFestasi, 2021)
Universities not only provide theoretical reinforcement to students, in this era of technological disruption and globalization, universities should provide facilities and opportunities for students to apply the theory they have learned. In any study program, the interests and entrepreneurial skills of these students are good. can be channeled. The university must be able to transform student entrepreneurship through intellectual capital and build business incubators in order to provide students with a better experience. This study uses a quantitative approach, by distributing questionnaires to 72 business incubators in Jakarta, Tangerang and surrounding areas. The results show that learning entrepreneurship theory will become intellectual capital if the university builds a business incubator as a training ground for its students